Design and Build Operational Amplifier Practicum Trainer Based on IC Tl084 and 741 - Ahmad saputra Surna Riah; Jeki saputra; Kasiyanto (Journal of Creative Power and Ambition (JCPA), 2026)
The op amp amplifier is a very important component in electronics education. because, there is nothing more fundamental in teaching electronics than the op-amp (operational amplifier). This research is used to analyze op amp circuits with a focus on their performance characteristics and versatility in various configurations such as inverting, non-inverting, summing inverting, summing non-inverting amplifiers. This practical tool requires several supporting tools such as a power supply as a voltage input and an Oscilloscope as a wave reader, input, and output from the circuit in practice, using a laptop with the livewire application which is used to carry out the simulation first before carrying out the practice and several other supporting tools. The aim of this research is to design and create a practical application for Op-amps (Operational Amplifiers) based on IC TL084 and IC 741. The use of practical modules based on Op-Amp ICs is expected to provide direct experience that is relevant to real applications in the industrial world, such as sensor signal processing, health monitoring devices (EKG and EEG), Audio Amplifiers, Motor controllers, and others.